Computational analysis of missense mutations in squalene epoxidase associated with terbinafine resistance in clinically reported dermatophytes - Hussein R. Mahmood; Masoomeh Shams-Ghahfarokhi; Mehdi Razzaghi-Abyaneh (Scientific Reports)
Abstract Dermatophyte infections, as a significant public health threats, are increasingly associated with antifungal drug resistance, particularly to terbinafine. Mutations in the squalene epoxidase (SQLE) gene have been linked to resistance by altering amino acid residues and interfering with drug-protein interactions. This study applied computational tools including I-Mutant, ConSurf, HOPE, DynaMut2, STRING, and molecular docking to assess the structural and functional impact of clinically reported SQLE missense mutations in terbinafine-resistant dermatophyte isolates. Twelve out of fourteen mutations significantly reduced SQLE stability, with L393F, L393S, and F397L identified as the most destabilizing. ConSurf analysis revealed that residues F311, L393S, L393F, F397I, L437P, H440Y, and H440T were highly conserved, structurally buried, and essential for SQLE integrity, while V237I, F397L, and F415S were conserved but less critical. Notably, Q408L was identified as functionally significant and surface-exposed, underscoring its potential as a key contributor to resistance. Conserved regions were found to be more susceptible to functional disruption than non-conserved ones. HOPE analysis highlighted changes in size, charge, and hydrophobicity in the mutant residues, suggesting potential disruption of SQLE’s functional architecture. Also, DynaMut2 analysis predicted decreased flexibility and stability in most mutants. Molecular docking identified altered binding pockets in four variants F397L, L437P, F415V, and Y394N compared to the wild-type, potentially compromising terbinafine binding. STRING network analysis revealed functional interactions between SQLE and ten proteins involved in ergosterol biosynthesis. These findings offer valuable molecular insights into terbinafine resistance mechanisms and identify conserved, mutation-sensitive sites that may guide antifungal drug development and resistance management strategies.